"Feeling of what happens: body, emotion and the making of consciousness" - "Damasio, Antonio" (London, 2000)
A new theory of consciousness and the construction of identity focuses on the body's reaction to its world, postulating that a complex relationship between body, emotion, and mind is required to configure the self.
Keywords: Consciousness